Region Based Image Retrieval Using Ratio of Proportional Overlapping Object - Agus Zainal Arifin; Rizka Wakhidatus Sholikah; Dimas Fanny H. P.; Dini Adni Navastara (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
In Region Based Image Retrieval (RBIR), determination of the relevant block in query region is based on the percentage of image objects that overlap with each sub-blocks. But in some images, the size of relevant objects are small. It may cause the object to be ignored in determining the relevant sub-blocks. Therefore, in this study we proposed a system of RBIR based on the percentage of proportional objects that overlap with sub-blocks. Each sub-blocks is selected as a query region. The color and texture features of the query region will be extracted by using HSV histogram and Local Binary Pattern (LBP), respectively. We also used shape as global feature by applying invariant moment as descriptor. Experimental results show that the proposed method has average precision with 74%.